Low-cost hydrothermal synthesis and characterization of pentanary Cu2ZnxNi1−xSnS4 nanoparticle inks for thin film solar cell applications. (1st June 2017) - Babu, G. Sahaya Dennish; Shajan, X. Sahaya; George, Alphy; Parameswaran, P.; Murugesan, S.; Divakar, R.; Mohandas, E.; Kumaresan, S.; Rao, G. Mohan
Abstract: In the present investigation, Cu2 (Zn x Ni1- x )SnS4 nanoparticles were successfully synthesized by facile and low-cost hydrothermal method for different concentration of x =1, 0.75, 0.50, 0.25, 0 at 190 °C for 24 h. The probable reaction mechanism for the formation of Cu2 Zn x Ni1- x SnS4 nanoparticles is reported. The synthesized nanoparticles were characterized by x-ray diffraction (XRD), Raman spectroscopy, field emission scanning electron microscope (FESEM), transmission electron microscope (TEM), x-ray photoelectron spectroscopy (XPS) and ultra violet-visible (UV–vis) spectrometric studies. The phase pure kesterite and stannite structures of synthesized nanoparticles were confirmed by XRD and Raman spectroscopy analysis. The structural transition from tetragonal kesterite copper zinc tin sulfide (Cu2 ZnSnS4 - CZTS) to stannite Cu2 Zn x Ni1- x SnS4 ( x =0) occurs in the Cu2 Zn x Ni1- x SnS4 samples with nickel concentration ( x ) in the range of 0.25–1. The results of SEM and TEM show the morphological features of the prepared Cu2 Zn x Ni1- x SnS4 nanoparticles. The optical band gaps of the prepared Cu2 Znx Ni1- x SnS4 nanoparticles were reduced from 1.63 eV ( x =1) to 1.36 eV ( x =0). It falls well within the suitable band gap range of absorber materials to be useful for thin film solar cell applications. Photoresponse behavior of Cu2 Zn x Ni1- x SnS4 ( x =1 and 0.75) thin films under dark and light illumination indicates the potential of Cu2 Zn x Ni1- x SnS4 nanoparticles as an alternate absorber material in low-cost thin film solar cells applications. Graphical abstract: Highlights: Pentanary chalcogenide nanoparticles have been synthesized by a hydrothermal method. Optical band gap was tuned from 1.63 eV (Cu2 Zn x Ni1- x SnS4 ; x =1) to 1.36 eV ( x =0). Photoresponse of the thin films show significant current enhancement.